Pengaruh Modal Intelektual, Ukuran Perusahaan, dan Leverage terhadap Nilai Perusahaan: Profitabilitas sebagai Mediasi pada Perusahaan LQ45 (2019–2023) - Syafiah Syafiah; Anwar Azazi; Anggraini Syahputri; Uray Ndaru Mustika (eCo-Buss, 2025)
The fluctuation of company value (reflected in stock prices) amidst fierce business competition and the importance of strategic adaptation in the digital era. This study aims to analyse the extent to which Intellectual Capital, Firm Size, and Leverage influence Firm Value with Profitability as a mediator. The sample consists of 28 LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, resulting in 119 panel data observations after outlier treatment. The analysis, conducted with rigorous methodology, utilizes multiple linear regression and path analysis (SPSS 27). The findings reveal that intellectual capital positively influences Profitability, while firm size and leverage significantly adversely affect Profitability. Intellectual capital and firm size significantly negatively impact firm value, while leverage does not considerably affect firm value. Profitability plays a crucial role in enhancing firm value and effectively mediates the relationships between the three independent variables and firm value. The research implications highlight challenges in communicating or realizing the full value of these intangible assets in the market, as well as indicating that large scale and the utilization of leverage do not always guarantee superior financial performance.